PEM hydrogen production membrane electrode and preparation method thereof

By adding conductive enhancer to the anode catalytic layer of the PEM hydrogen-making film electrode and forming a gradient structure, the problem of ohmic overpotential increase in the prior art is solved, and higher electrolytic efficiency and lower hydrogen-making cost are achieved.

CN119913566APending Publication Date: 2025-05-02BEIJING SMART ENERGY RES INST +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411243562.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

When the existing PEM hydrogen-making membrane electrodes improve catalytic activity and water-gas transport characteristics, they pay less attention to the reduction of ohmic overpotentials, resulting in the failure to effectively solve the electrolytic efficiency and cost problems.

Method used

By adding conductive enhancer to the anode catalytic layer and controlling its content to increase stepwise or continuously from the near-film side to the distal side, a gradient structure is formed to reduce ohmic impedance and improve electron transport efficiency.

Benefits of technology

A significant reduction in ohmic impedance is achieved, the electrochemical performance of the membrane electrode is improved, and the electrolytic energy consumption and hydrogen production cost are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119913566A_ABST
    Figure CN119913566A_ABST
Patent Text Reader

Abstract

The invention discloses a PEM hydrogen production membrane electrode and a preparation method thereof. The membrane electrode comprises a proton exchange membrane, an anode catalyst layer and a cathode catalyst layer, the anode catalyst layer comprises a catalyst, an ionomer and a conductive reinforcing agent, and the content of the conductive reinforcing agent is increased from the membrane near side to the membrane far side of the anode catalyst layer; the content of the conductive reinforcing agent is increased in a stepped manner, a continuous manner or a combination of the two increasing manners. According to the preparation method of the PEM hydrogen production membrane electrode, an anode catalyst layer of the membrane electrode is formed by coating slurry containing different contents of conductive reinforcing agents layer by layer. The PEM hydrogen production membrane electrode provided by the invention not only meets the requirement of enhancing electron transmission, but also effectively reduces the adverse effect of the conductive enhancer on high-density proton conduction on the near-membrane side.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of PEM hydrogen production membrane electrodes, and in particular, the present invention relates to a PEM hydrogen production membrane electrode and a preparation method thereof. Background Art

[0002] Proton exchange membrane water electrolysis (PEM hydrogen production) technology has the advantages of good adaptability to green electricity fluctuations, high electrolysis efficiency, fast response speed, and low hydrogen-oxygen interpenetration rate. It is a highly promising water electrolysis hydrogen production technology, but the cost and stability of PEM hydrogen production are still the key issues limiting its large-scale commercialization. Reducing electrolysis energy consumption and improving electrochemical performance are currently urgent issues to be solved. Membrane electrode (MEA) is a key component of PEM hydrogen production equipment, which is directly related to the hydrogen production efficiency and cost of electrolysis equipment. The three polarization indicators of the membrane electrode, ohmic polarization, activation polarization, and mass transfer polarization, are crucial to the electrolysis efficiency of the entire electrolyzer. The higher the polarization, the higher the electrolysis overpotential, the higher the energy consumption, and the more unfavorable the hydrogen production efficiency and cost. Therefore, to improve the electrolysis performance of the electrolyzer, it is necessary to reduce the three polarization indicators. The conductivity of the membrane electrode catalyst layer is not only directly related to the ohmic polarization, but also affects the activation polarization. Its structural design needs to consider issues such as improving catalyst utilization, reducing ohmic impedance, and enhancing mass transfer.

[0003] Although catalyst performance has been greatly improved in the past 100 years of research, most of the catalysts with excellent performance in the three-electrode system have not shown equivalent performance improvement in MEA. This is because it is difficult for the same catalyst to have both activity, conductivity and stability. For example, metal element catalysts (such as iridium black, ruthenium black, etc.) have high electrocatalytic activity, but poor electrochemical stability under strong acid and high overpotential, while metal oxide (iridium oxide, ruthenium oxide, etc.) catalysts have high stability, but their conductivity is relatively weak.

[0004] Therefore, optimizing the catalytic layer structure to prepare high-performance MEA, making full use of existing catalysts, giving full play to their activity, reducing catalyst loading and energy consumption, is of great practical significance for promoting cost reduction and efficiency improvement in the field of PEM hydrogen production technology.

[0005] Patent US20120121994A1 discloses a membrane electrode assembly, in which a layer of electrocatalyst particles is embedded in the near-boundary layer of the membrane to obtain a membrane electrode, the membrane electrode having a porosity that allows gas to flow through the electrode, and the surface roughness of the membrane electrode increases the catalytic active area of ​​the electrode, and the roughness and permeability of the metallization layer lead to a thicker electrode, which can lead to a larger catalytic active area and improve water management at the cathode. However, the patent focuses on the porosity and surface roughness of the membrane electrode, that is, water vapor transmission and activation area, and does not pay attention to the ohmic polarization characteristics.

[0006] Patent CN117535710A discloses a PEM electrolyzer membrane electrode, which uses a roller with a convex shape to roll the catalyst layer during the preparation process, and controls the protrusion depth of the roller to be <5um, the width to be <50um, and the spacing to be <50um. The cathode catalyst layer and the anode catalyst layer finally obtained have a protruding uniform shape, thereby increasing the contact active area of ​​the cathode catalyst layer and the anode catalyst layer. However, the patent does not focus on the ohmic overpotential of the catalyst layer.

[0007] Patent CN111740122A discloses an ordered membrane electrode, which utilizes the external field driving force of electrochemical deposition to cause the active components to undergo redox reactions on the surface of the gas diffusion layer, so that the catalyst grows in situ on the surface of the gas diffusion layer, thereby obtaining a catalytic layer with a three-dimensional multi-level structure. The catalytic layer with a three-dimensional multi-level structure has a higher active area. This patent only focuses on the structure of the catalytic layer, and also does not focus on the ohmic polarization characteristics.

[0008] It can be seen that there are currently many patents on membrane electrodes, but these patents mainly focus on improving the water vapor transport characteristics of membrane electrodes or increasing the active area, and pay less attention to improving the ohmic overpotential. The electrochemical performance of membrane electrodes needs to be improved urgently. Summary of the invention

[0009] Based on this, the present invention aims to overcome at least one defect of the prior art and provide a PEM hydrogen production membrane electrode and a preparation method thereof.

[0010] In a first aspect, the present invention relates to a PEM hydrogen production membrane electrode, wherein the membrane electrode comprises a proton exchange membrane, an anode catalyst layer and a cathode catalyst layer, wherein the anode catalyst layer comprises a catalyst, an ionomer and a conductivity enhancer, wherein the content of the conductivity enhancer increases from the near-membrane side to the far-membrane side of the anode catalyst layer, and the increase in the content of the conductivity enhancer is a step-like increase, a continuous increase or a combination of the two increase methods.

[0011] In a second aspect, the present invention relates to a method for preparing a PEM hydrogen production membrane electrode, wherein the anode catalyst layer of the membrane electrode is formed by coating a slurry containing different contents of a conductive enhancer layer by layer.

[0012] Although the gradient coating of catalysts with different conductivity can also achieve the effect of reducing ohmic impedance similar to that of this method. But in fact, in the electrolysis of water, considering the corrosion of high potential and strong acid environment, most of the catalysts used are metal oxides, and these oxide catalysts are difficult to adjust their own conductivity on the basis of ensuring their own activity and durability. In other words, improving the conductivity of electrolytic hydrogen production catalysts is very challenging to ensure the performance of the catalyst and the preparation process and method of the catalyst. The method in the patent of the present invention can easily achieve a significant reduction in ohmic impedance by adding a conductive enhancer and adjusting the coating process.

[0013] Therefore, the beneficial effect of the present invention is that the PEM hydrogen production membrane electrode described in the present invention controls the increase of the conductivity enhancer from the near-membrane side to the far-membrane side of the anode catalyst layer, which not only meets the demand for enhanced electron transmission, but also effectively reduces the adverse effects of the conductivity enhancer on high-density proton conduction on the near-membrane side. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 This is a schematic diagram of the PEM hydrogen production membrane electrode structure of the present invention. DETAILED DESCRIPTION

[0015] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific implementation methods.

[0016] Regarding the first aspect of the present invention, the catalytic layer where the electrode reaction occurs is a key component of the PEMWE. The microscopic, mesoscopic and macroscopic multi-level structures of the membrane electrode catalytic layer are the key to improving the electrochemical surface area and the effective transmission of protons, electrons, water, product gas and heat. Its structural design needs to consider issues such as improving catalyst utilization, reducing ohmic impedance, and enhancing mass transfer. The catalytic layer is usually composed of a catalyst (providing active sites and electron transport pathways), an ionomer (providing H + The catalytic layer consists of a continuous cross-network structure composed of nanostructured carbon nanotubes (transport paths and act as a binder to enhance the mechanical properties of the catalytic layer) and pores (providing transport paths for reaction water and product gas), providing a reaction site for the electrochemical reaction. Therefore, the effective catalytic layer network structure not only depends on the catalyst activity, but is also closely related to the accessibility of the active sites to reaction water, protons and electrons. Figure 1 As shown, the PEM hydrogen production membrane electrode of the present invention includes a mass exchange membrane 1, an anode catalyst layer 2 and a gas transfer layer 3. The present invention adds a conductivity enhancer to the anode catalyst layer 2, and the content of the conductivity enhancer increases from the anode near-membrane side to the anode far-membrane side, so as to meet the conduction demand of higher electron density gradually increasing from the near-membrane side to the outside, and by enhancing the electronic conductivity of each part of the catalyst layer, more active sites are fully utilized, thereby reducing activation polarization, and thus ultimately greatly improving the electrochemical performance of the membrane electrode.

[0017] In one preferred embodiment, the increase in the content of the conductive enhancer is a step-like increase or a continuous increase, which can be a combination of the two increase modes. The so-called combination can be a step-like increase in some areas and a continuous increase in some areas, and these areas can be distributed overlappingly.

[0018] In one preferred embodiment, the conductivity enhancer comprises one or more of a metal element, an alloy, a metal-based solid solution or an intermetallic compound.

[0019] In one preferred embodiment, the conductivity enhancer is one or more of platinum-gold alloy, platinum-nickel-palladium alloy, TiN, Ni-palladium-gold alloy or Ni2P.

[0020] In one preferred embodiment, the metal-based solid solution or intermetallic compound is doped with other elements.

[0021] In one preferred embodiment, the conductivity enhancer has strong conductivity.

[0022] In one preferred embodiment, in each gradient structure, the content of the conductive enhancer is 0.1%-40% of the catalyst content, preferably, the content of the conductive enhancer is 1%-30%, more preferably, the content of the conductive enhancer is 2-20%, or, the content of the conductive enhancer is 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 5%, 16%, 17%, 18%, 19%.

[0023] In one preferred embodiment, the content of the catalyst may change gradually or continuously from the near-membrane layer to the far-membrane side, or may remain unchanged.

[0024] In one preferred embodiment, the catalyst is an iridium-based, iridium-oxide-based, ruthenium-based or ruthenium-oxide-based compound or mixture.

[0025] In one preferred embodiment, the membrane electrode has a current density of 2A / cm 2 The electrolysis voltage is less than or equal to 1.86V, preferably, less than or equal to 1.85V, 1.84V, 1.83V, 1.82V.

[0026] Regarding the second aspect of the present invention, for the preparation method of the PEM hydrogen production membrane electrode, in one preferred embodiment, the preparation method comprises the following steps:

[0027] (1) Prepare slurry, prepare slurry 1 to slurry N as needed, where N ≥ 2, the gradient level is consistent with the number of slurries, and the content of the conductive enhancer in slurry 1 to slurry N increases in sequence:

[0028] (2) Membrane electrode coating: Slurry 1 to slurry N are coated on the proton exchange membrane in sequence.

[0029] The N is 2, 3, 4, 5, 6, 7, 8, 9, 10 or more, for example, 12, 15, 18, 20, 25, etc.

[0030] By controlling the amount of slurry used for coating, a gradient increase or continuous increase in the content of the conductive enhancer can be obtained. When the amount of slurry is large, for example, when N is above 10, coupled with the diffusion of the conductive enhancer during the preparation process, a continuous increase in the content of the conductive enhancer can be achieved. In addition, the change in the coating temperature of each layer can also be controlled to adjust the diffusion of the conductive enhancer, resulting in a continuous change in the content of the conductive enhancer.

[0031] In one preferred embodiment, the solvent used in the slurry is a mixed solvent of an organic solvent and water, wherein the volume ratio of water to the organic solvent is 1-5:5-9.

[0032] In one preferred embodiment, the slurry comprises a catalyst and an ionomer, wherein the content of the catalyst and the ionomer are both 0.05 mg / ml-100 mg / ml.

[0033] In one preferred embodiment, the coating is at least one of spray coating, blade coating, slit coating, roll-to-roll coating, and micro-concave coating.

[0034] In one preferred embodiment, the coating comprises repeatedly coating one slurry to a desired thickness, and then sequentially coating subsequent slurries.

[0035] Example

[0036] The embodiments of the present invention are only used for illustrative description and should not be construed as limiting the present invention.

[0037] For simplicity, only some numerical ranges are explicitly disclosed herein. However, any lower limit can be combined with any upper limit to form an unambiguous range; and any lower limit can be combined with other lower limits to form an unambiguous range, and any upper limit can be combined with any other upper limit to form an unambiguous range. In addition, although not explicitly stated, each point or single value between the range endpoints is included in the range. Thus, each point or single value can be combined with any other point or single value as its own lower limit or upper limit or with other lower limits or upper limits to form an unambiguous range.

[0038] The above application content of the present invention is not intended to describe each disclosed embodiment or each implementation in the present invention. The following description more specifically illustrates exemplary embodiments. In many places throughout the application, guidance is provided by a series of examples, which can be used in various combinations. In each example, enumeration is only used as a representative group and should not be interpreted as exhaustive.

[0039] Unless otherwise specified, the raw materials used in the following examples are common commercially available products.

[0040] Example 1

[0041] A PEM hydrogen production membrane electrode, the preparation process of which is as follows:

[0042] 1) Prepare two slurries, A and B. Both slurries use iridium oxide as a catalyst, and the conductivity enhancer is a platinum alloy. The total content of the catalyst and the ionomer in the slurry is 3 mg / mL, and the volume ratio of water to isopropanol in the solvent is 3:7. Among them, the mass of the catalyst in the A slurry is 0.2783g, the amount of platinum alloy added is 1% of the mass of the catalyst, the mass of the nafion solution is 0.48g, and the total volume of water and isopropanol is 93mL; the mass of the catalyst in the B slurry is 0.2783g; the amount of platinum alloy added is 5% of the mass of the catalyst, and the mass of the nafion solution is 0.48g.

[0043] 2) The membrane electrode was prepared by ultrasonic atomization spraying, using a 127 μm thick perfluorosulfonic acid resin membrane and a catalyst loading of 1.3 mg / cm 2 . The coating area is 25cm 2 First, 20 layers of slurry A are sprayed, and then 12 layers of slurry B are sprayed to obtain a membrane electrode.

[0044] Example 2

[0045] A PEM hydrogen production membrane electrode, the preparation process of which is as follows:

[0046] 1) Prepare two slurries, A and B. Both slurries use iridium oxide as a catalyst, and the conductivity enhancer is a Ni2P compound. The total content of the catalyst and ionomer in the slurry is 3 mg / mL, and the volume ratio of water to isopropanol in the solvent is 3:7. Among them, the mass of the catalyst in slurry A is 0.2783 g, the amount of Ni2P added is 3% of the mass of the catalyst, the mass of the nafion solution is 0.6 g, and the total volume of water and isopropanol is 93 mL; the mass of the catalyst in slurry B is 0.2783 g; the amount of Ni2P added is 5% of the mass of the catalyst, and the mass of the nafion solution is 0.6 g.

[0047] 2) The membrane electrode was prepared by ultrasonic atomization spraying, using a 127 μm thick perfluorosulfonic acid resin membrane and a catalyst loading of 1.3 mg / cm 2 . The coating area is 25cm 2 First, 20 layers of slurry A are sprayed, and then 12 layers of slurry B are sprayed to obtain a membrane electrode.

[0048] Example 3

[0049] A PEM hydrogen production membrane electrode, the preparation process of which is as follows:

[0050] 1) Prepare three slurries A, B, and C. All three slurries use iridium / iridium oxide as catalysts, and the conductivity enhancer is platinum-palladium alloy. The total content of the catalyst and ionomer in the slurry is 1.5 mg / mL, and the volume ratio of water to isopropanol in the solvent is 2:8. Among them, the mass of the catalyst in the A slurry is 0.1855 g, the amount of platinum-palladium alloy added is 0% of the mass of the catalyst, the mass of the nafion solution is 0.36 g, and the total volume of water and isopropanol is 124 mL; the mass of the catalyst in the B slurry is 0.1855 g; the amount of platinum-palladium alloy added is 5% of the mass of the catalyst, the mass of the nafion solution is 0.36 g, and the amount of water and isopropanol added is the same as that of the A slurry; the mass of the catalyst in the C slurry is 0.1855 g, the amount of platinum-palladium alloy added is 10% of the mass of the catalyst, the mass of the nafion solution is 0.36 g, and the amount of water and isopropanol added is the same as that of the A slurry.

[0051] 2) The membrane electrode was prepared by ultrasonic atomization spraying, using a 127 μm thick perfluorosulfonic acid resin membrane and a catalyst loading of 1.3 mg / cm 2 . The coating area is 25cm 2 First, 10 layers of slurry A are sprayed, then 12 layers of slurry B are sprayed, and then 10 layers of slurry C are sprayed to obtain a membrane electrode.

[0052] Example 4

[0053] A PEM hydrogen production membrane electrode, the preparation process of which is as follows:

[0054] 1) Four slurries A, B, C, and D were prepared. Ruthenium / ruthenium oxide was used as a catalyst in all four slurries, and TiN was used as a conductivity enhancer. The total content of the catalyst and the ionomer in the slurry was 1.5 mg / mL, and the volume ratio of water to isopropanol in the solvent was 1:9. Among them, the mass of catalyst in slurry A is 0.1855g, TiN is 2% of the catalyst, the mass of nafion solution is 0.60g, and the total volume of water and isopropanol is 93mL; the mass of catalyst in slurry B is 0.1855g; TiN is 3% of the catalyst, the mass of nafion solution is 0.36g, and the amount of water and isopropanol added is the same as that of slurry A; the mass of catalyst in slurry C is 0.1855g, the amount of TiN added is 10% of the catalyst mass, the mass of nafion solution is 0.60g, and the amount of water and isopropanol added is the same as that of slurry A; the mass of catalyst in slurry D is 0.1855g, the amount of TiN added is 15% of the catalyst mass, the mass of nafion solution is 0.60g, and the amount of water and isopropanol added is the same as that of slurry A.

[0055] 2) The membrane electrode was prepared by ultrasonic atomization spraying, using a 127 μm thick perfluorosulfonic acid resin membrane and a catalyst loading of 2 mg / cm 2 . The coating area is 25cm 2 . The membrane electrode is obtained by spraying 5 layers of slurry A, 12 layers of slurry B, 10 layers of slurry C, and 5 layers of slurry D in sequence.

[0056] Example 5

[0057] A PEM hydrogen production membrane electrode, the preparation process of which is as follows:

[0058] 1) Prepare two slurries, A and B. Both slurries use iridium oxide as a catalyst, and the conductivity enhancer is palladium-gold alloy. The total content of the catalyst and ionomer in the slurry is 30 mg / mL, and the volume ratio of water to isopropanol in the solvent is 3:7. Among them, the mass of the catalyst in slurry A is 0.2783 g, the amount of palladium-gold alloy added is 1% of the mass of the catalyst, the mass of nafion solution is 0.48 g, and the total volume of water and isopropanol is 93 mL; the mass of the catalyst in slurry B is 0.2783 g; the amount of palladium-gold alloy added is 5% of the mass of the catalyst, and the mass of nafion solution is 0.48 g.

[0059] 2) The membrane electrode was prepared by blade coating, using a 127 μm thick perfluorosulfonic acid resin membrane and a catalyst loading of 1.3 mg / cm 2 . The coating area is 25cm 2 First, apply slurry A, and after the first layer is dried, apply slurry B to obtain a membrane electrode.

[0060] Comparative Example 1

[0061] A PEM hydrogen production membrane electrode, the preparation process of which is as follows:

[0062] 1) Prepare slurry A, use iridium oxide as catalyst, platinum alloy as conductivity enhancer, the total content of catalyst and ionomer in the slurry is 3 mg / mL, and the volume ratio of water to isopropanol in the solvent is 3:7. Among them, the mass of catalyst in slurry A is 0.2783 g, the amount of platinum alloy added is 5% of the mass of catalyst, the mass of nafion solution is 0.48 g, and the total volume of water and isopropanol is 93 mL.

[0063] 2) The membrane electrode was prepared by ultrasonic atomization spraying, using a 127 μm thick perfluorosulfonic acid resin membrane and a catalyst loading of 1.3 mg / cm 2 . The coating area is 25cm 2 . 20 layers of slurry A were sprayed to obtain a membrane electrode.

[0064] Comparative Example 2

[0065] A PEM hydrogen production membrane electrode, the preparation process of which is as follows:

[0066] 1) Prepare slurry A, using iridium oxide as a catalyst, without a conductive enhancer, the total content of the catalyst and ionomer in the slurry is 3 mg / mL, and the volume ratio of water to isopropanol in the solvent is 3:7. Among them, the mass of the catalyst in slurry A is 0.2783 g, the mass of the nafion solution is 0.48 g, and the total volume of water and isopropanol is 93 mL.

[0067] 2) The membrane electrode was prepared by ultrasonic atomization spraying, using a 127 μm thick perfluorosulfonic acid resin membrane and a catalyst loading of 1.3 mg / cm 2 . The coating area is 25cm 2 . 20 layers of slurry A were sprayed to obtain a membrane electrode.

[0068] The membrane electrode described in Examples 1 to 5 and Comparative Examples 1 and 2 was subjected to a performance test. The membrane electrode electrolysis performance test was performed using a single cell fixture at a current density of 2 A / cm 2 , the reaction temperature is 50°C, and the test results are shown in Table 1.

[0069] Table 1

[0070]

[0071]

[0072] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the technical solution of the present invention, and are not intended to limit the specific implementation methods of the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the claims of the present invention shall be included in the protection scope of the claims of the present invention.

Claims

1. A PEM hydrogen production membrane electrode, the membrane electrode comprising a proton exchange membrane, an anode catalyst layer and a cathode catalyst layer, characterized in that: The anode catalyst layer includes a catalyst, an ionomer and a conductivity enhancer, wherein the content of the conductivity enhancer increases from the membrane-proximal side to the membrane-distal side of the anode catalyst layer, and the increase in the content of the conductivity enhancer is a step-like increase, a continuous increase or a combination of the two increase modes.

2. The PEM hydrogen production membrane electrode according to claim 1, characterized in that: The conductivity enhancer comprises one or more of a metal element, an alloy, a metal-based solid solution or an intermetallic compound. Optionally, the metal-based solid solution or the intermetallic compound is doped with other elements.

3. The PEM hydrogen production membrane electrode according to claim 2, characterized in that: The gradient level in the gradient increase is ≥ 2; and / or the conductivity enhancer is one or more of platinum-gold alloy, platinum-palladium alloy, TiN, palladium-gold alloy or Ni2P.

4. The PEM hydrogen production membrane electrode according to any one of claims 1 to 3, characterized in that: In each gradient structure, the content of the conductivity enhancer is 0.1%-40% of the content of the catalyst, preferably, the content of the conductivity enhancer is 1%-30%, more preferably, the content of the conductivity enhancer is 2%-20%.

5. The PEM hydrogen production membrane electrode according to any one of claims 1 to 3, characterized in that: The catalyst is an iridium-based, iridium-oxide-based, ruthenium-based or ruthenium-oxide-based compound or mixture.

6. The PEM hydrogen production membrane electrode according to any one of claims 1 to 3, characterized in that: The membrane electrode is at a current density of 2A / cm 2 The electrolysis voltage is less than or equal to 1.86V.

7. A method for preparing a PEM hydrogen production membrane electrode according to any one of claims 1 to 6, characterized in that: The steps include: The anode catalyst layer of the membrane electrode is formed by coating a slurry containing different contents of a conductive enhancer.

8. The preparation method according to claim 7, characterized in that: The preparation method comprises the following steps: (1) Prepare slurry, prepare slurry 1 to slurry N as needed, where N ≥ 2, the gradient level is consistent with the number of slurries, and the content of the conductive enhancer in slurry 1 to slurry N increases in sequence: (2) Membrane electrode coating: Slurry 1 to slurry N are coated on the proton exchange membrane in sequence.

9. The preparation method according to claim 7, characterized in that: The solvent used in the slurry is a mixed solvent of an organic solvent and water, wherein the volume ratio of water to the organic solvent is 1-5:5-9, and / or the slurry contains a catalyst and an ionomer, wherein the contents of the catalyst and the ionomer are 0.05 mg / ml-100 mg / ml, respectively, and / or the coating is at least one of spraying, blade coating, slit coating, roll-to-roll coating, and micro-concave coating.

10. The method for preparing a PEM hydrogen production membrane electrode according to claim 7, characterized in that: The coating includes repeatedly coating one slurry to a desired thickness and then sequentially coating subsequent slurries.

Citation Information

Patent Citations

  • Membrane And Catalyst Composite For Membrane Electrode Assembly

    US20120121994A1